2021
DOI: 10.1186/s12903-021-01762-2
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of the effect of probiotic lactobacillus reuteri on peri-implantitis microflora

Abstract: Background Probiotics affect both the development and stability of microbiota by altering the colonization of pathogens and thus helps in stimulating the immune system of the individual. The aim of the present study is to assess the effect of probiotics on peri-implantitis microflora, by determining the minimum inhibitory concentration (MIC) of Lactobacillus reuteri, that can be effectively administered as an antimicrobial agent on specific peri-implantitis pathogens. Hence, this study will be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…When compared to periodontitis, tissue destruction was significantly higher among individuals with peri-implantitis. Although various treatment options are available, limited evidence is present on the usage of probiotics for the treatment of peri-implant diseases [ 11 , 12 ]. Thus, this study was carried out to evaluate the in vitro effect of probiotic L. salivarius on peri-implantitis pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…When compared to periodontitis, tissue destruction was significantly higher among individuals with peri-implantitis. Although various treatment options are available, limited evidence is present on the usage of probiotics for the treatment of peri-implant diseases [ 11 , 12 ]. Thus, this study was carried out to evaluate the in vitro effect of probiotic L. salivarius on peri-implantitis pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the minimal inhibitory volume of the L. reuteri AN417 CFS able to reduce the pathogen growth rate and viability was 10% ( v/v ) against P. gingivalis and 20% ( v/v ) against F. nucleatum [ 23 ]. Mulla and colleagues also observed that P. gingivalis directly isolated from the patients’ dental plaque was sensitive to the treatment with the L. reuteri probiotic [ 24 ]. Other authors have demonstrated that the CFS of fermented sausage-derived L. reuteri strains also had antibacterial properties due to lactic acid and low pH, emphasizing once more the capability of each strain to exhibit specific metabolites [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Over the years, implants have become the treatment of choice for replacing missing tooth [ 13 , 14 ]. Researchers have studied the effect of immediate and delayed implant loading into the extracted site on the QoL in pre- and post-insertion period.…”
Section: Reviewmentioning
confidence: 99%